Industrial water treatment with heavy metals through zeolites and bioremediation systems with aquatic plants especially Eichhornia crassipes. State of art review (2014)
In this review we explore different opportunities to use a cheap natural material for removing and retention of heavy metals from polluted waters by waste of different processes. Two research systems will be addressed: the first through a material known as zeolite or more generally porous  luminosilicates, which may be synthesized or extracted from the mines of clays and minerals, being used in its natural state or after modification processes and doping. The other mechanism is bioremediation through algae, some bacteria and especially aquatic plants such as Eichhornia crassipes (water hyacinth). We will evaluate the viability of joining these two types complementing each other. Investigations into the feasibility of Eichhornia crassipes (water hyacinth) as feedstock for biofuels are also reviewed.